Precision of Classification of Odorant Value by the Power of Olfactory Bulb Oscillations Is Altered by Optogenetic Silencing of Local Adrenergic Innervation - Ramirez-Gordillo, Daniel; Ma, Ming; Restrepo, Diego (Frontiers in Cellular Neuroscience, 2018)
Neuromodulators such as noradrenaline appear to play a crucial role in learning and memory. The goal of this study was to determine the role of norepinephrine in representation of odorant identity and value by olfactory bulb oscillations in an olfactory learning task. We wanted to determine whether the different bandwidths of olfactory bulb oscillations encode information involved in associating the odor with the value, and whether norepinephrine is involved in modulating this association. To this end mice expressing halorhodopsin under the dopamine-beta-hydrolase (DBH) promoter received an optetrode implant targeted to the olfactory bulb. Mice learned to differentiate odorants in a go-no-go task. A receiver operating characteristic analysis showed that there was development of a broadband differential rewarded vs. unrewarded odorant-induced change in the power of local field potential oscillations as the mice became proficient in discriminating between two odorants. In addition, the change in power reflected the value of the odorant rather than the identity. Furthermore, optogenetic silencing of local noradrenergic axons in the olfactory bulb altered the differential oscillatory power response to the odorants for the theta, beta and low gamma bandwidths.